(untitled) (Journal of Advanced Research in Social Sciences, 2019)
This paper presents the postcolonial theory and its emergence from the fallout of colonial impact on the world after WWII. It reveals insight into historical actualities and traces the sequential line of thought and speculation of the period, how the issue of representation and self-determination is displayed in the theoretical argument. At that point, it clarifies the issue of identity in the postcolonial theoretical line and its critical role as the real issue of postcolonial theory. The paper additionally uncovers how scholars explore the situation of recognition and self-recognizable proof. Finally, it clarifies significant theorist contentions about identity independently and in agreement with the sequential course of events, for example, Frantz Fanon, Edward Said. It notes how every scholar viewed and hypothesized the issue of identity and to what extent these speculations are essential in postcolonial studies.